Modeling of diafiltration processes for demineralization of acid whey: an empirical approach - Román, A.; Vatai, Gy.; Ittzés, A.; Kovács, Z.; Czermak, Peter (My University, 2013)
In this paper, a mathematical model is provided to describe the dynamics of membrane diafiltration processes for desalting acid whey. A rich representation of the separation process is given due to the employment of concentration-dependent solute rejections in the design equations. We propose an experimental design and a suitable empirical method for parameter estimation. This technique supports the disciplined use of experimental data and reduces the number of necessary a-priori experiments. With the help of experimental data we demonstrate the power of the presented modeling method.
Keywords: Whey; Demineralisation; Nanofiltration; Diafiltration; Mathematical modelling